Pengaruh Regulasi Pemerintah, Akses Informasi, Persaingan Usaha terhadap Strategi Bisnis dan Kinerja Usaha Industri Kecil di Sulawesi Utara - Bambang Hermanto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims to assess and analyze the effect of government regulation, access to information, competition on business strategy and performance of small scale industries in North Sulawesi. Explanatory research was conducted on four categories of small businesses (manufacturing industry), namely: food and beverages, furniture, tekstile and convection, and silver metal, as many as 200 respondents (sample) were included in the survey using a questionnaire (questionnaire). Respondents are the owner and manager of the business. Sampling technique using a multi-stage random sampling with proportional allocation. This research was conducted in 6 districts (each of the three districts/cities) in North Sulawesi. To analyze the effect of government regulation, access to information, competition on business strategy and performance of small scale industries, use descriptive analysis methods and structural equation modeling (Structural Equation Modeling, SEM) by using the program AMOS (Analysis of Moment Structural). The research concludes that government regulation, and business competition significantly influence the business strategy's. Performance of small industrial businesses significantly affected by government regulation, business competition, through a business strategy. Research findings show that access to information does not significantly influence the business strategy and business performance. Enhancing the performance of small industrial businesses in North Sulawesi was relying on the benefits of differentiation strategy, pricing and promotion supported by a conducive government regulation as the prime mover.Keywords: Government regulation, information Access, competition, business strategy and business performance.